Ftir Characterization And Validation Of Secondary Metabolites In Leaf And Bark Extracts And Direct Powder Of Erinocarpus Nimmonii, An Endemic Plant (Applied Biological Research, 2023)
The presentstudy focused on the screening of therapeutically valuable secondary  metabolites and FTIR analysis of sequential leaf and bark extracts and direct  powder of Erinocarpus nimmonii Grah. ex Dalz., an endemic medicinal species  ndary metabolites were screened by using standard methods.FTIR spectral profiling of all extracts and powder was done, and matched with a set opeak values specific for each secondary metabolite. The phytochemical  screening showed the presence ofsaponin, terpenoids, steroids, triterpenoids, gum and mucilage, but not  alkaloids. The FTIprofile showed coinciding peak values specific for all the  biomolecules tested, except alkaloids. Further, the presence of bidesmosidic  triterpenoid saponin in leaf extract, alkyne in bark extract, and absence of  cyanide peak were disclosed. This simple, affordable, and novel approach of  secondary metabolite validation directs further advancement towards  fractionation, while the use of direct powder still expedites the procedure by  skipping the laborious extraction process. It enables the revelation of therapeutic  biomolecules capped on green metallic nanoparticles. To be concise, it is straightforward way to bridge the gap between the spectral profile of plants with the actual secondary metabolites they own.
Keywords: Erinocarpus nimmonii; FTIR spectral profiling; green metallic nanoparticle; phytochemical screening; secondary metabolites